Technologies For Developing Social Competence of Future Primary Class Teachers - Khamidova Barno Makhmudovna (Genius Journals, 2024)
In this article, the technologies for developing social competence in the training of future primary school teachers are studied.
Keywords: Social competence; technology; tool